Medically Unexplained Physical Symptoms in Hospitalized Patients: A 9-Year Retrospective Observational Study - Poloni, Nicola; Ielmini, Marta; Caselli, Ivano; Ceccon, Francesca; Bianchi, Lucia; Isella, Celeste; Callegari, Camilla (Frontiers in Psychiatry, 2018)
Introduction: “Medically unexplained physical symptoms” defines a subgroup of patients presenting physical symptoms of unclear origin. The study aims to profile clinical and sociodemographic characteristics of patients with MUPS. Materials and Methods: This 9-years observational retrospective study assesses patients admitted between 2008 and 2016 in the divisions of neurology and gastroenterology. Socio-demographic and clinical variables were evaluated: gender, age, diagnosis or diagnostic hypothesis, presence of psychiatric comorbidities, psychiatric evaluation, pharmacological treatment, number of admissions/visits. Results: Among 2,479 neurological patients 10.1% presented MUPS. Patients were more frequently female (63.5%), with a mean age of 50 years. Reported symptoms were headache (22.6%), seizures (8.7%), vertigo (5.9%), fibromyalgia (5.5%), paresthesia (5.1%), visual disturbances (5.1%), amnesia (3.9%). The diagnosis was somatoform disorder in 6.3% of cases, conversion disorder in 2.7%, and somatic symptom disorder in 1.5% only. 2,560 outpatients were evaluated in gastroenterology division. 9.6% (n=248) of patients had MUPS; 62.1% of them were female. The most affected age group ranged between 15 and 45 years. The most frequent diagnoses were functional abdominal pain (50%), dysmotility-like dyspepsia (26.6%), irritable bowel syndrome (10.4%), meteorism of unknown cause (2.4%), hiccup (1.6%), burning mouth syndrome (1.2%). No patients received a diagnosis of somatic symptom disorder. Discussion: Patients with MUPS are more often females, of middle age, with self-referred specific symptomatology. While neurological patients received a diagnostic-therapeutic approach in line with the literature, gastroenterological patients mainly received antipsychotics. A more comprehensive assessment and a development of psychoeducational interventions are needed to improve patients’ quality and quantity of life.